2020
DOI: 10.1161/strokeaha.120.030343
|View full text |Cite|
|
Sign up to set email alerts
|

Cysteine-Altering NOTCH3 Variants Are a Risk Factor for Stroke in the Elderly Population

Abstract: Background and Purpose: Cysteine altering NOTCH3 variants, which have previously been exclusively associated with the rare hereditary small vessel disease cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, have a population frequency of 1:300 worldwide. Using a large population database, and taking genotype as a starting point, we aimed to determine whether individuals harboring a NOTCH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 37 publications
7
35
1
Order By: Relevance
“…A recent report from the US Geisinger database suggested NOTCH3 variants are associated with an increased risk of stroke and MRI features of SVD, although no association was found with dementia. 8 Our findings are broadly confirmatory of those in the Geisinger cohort although we reported a slightly higher prevalence of NOTCH3 variants (0.22% vs 0.14%) and our larger sample size also allowed an association with vascular dementia to be detected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent report from the US Geisinger database suggested NOTCH3 variants are associated with an increased risk of stroke and MRI features of SVD, although no association was found with dementia. 8 Our findings are broadly confirmatory of those in the Geisinger cohort although we reported a slightly higher prevalence of NOTCH3 variants (0.22% vs 0.14%) and our larger sample size also allowed an association with vascular dementia to be detected.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in the subset of individuals in whom MRI scanning was performed, we correlated presence of NOTCH3 variants with MRI markers of SVD including white matter hyperintensities (WMHs) and lacunar infarcts and determined whether variant carriers had a similar spatial distribution of lesions to that seen in typical CADASIL cases. This study extends previous studies, particularly the Geisinger DiscovEHR cohort, 8 with a larger sample size providing greater power to examine associations with the risk of both stroke and dementia.…”
Section: Introductionsupporting
confidence: 76%
“…A very recent report from the United States Geisinger database suggested such variants associated with an increased risk of stroke and MRI features of SVD, although no association was found with dementia. [8] Our findings provide robust evidence from a large population-based study of over 200,000 individuals that common NOTCH3 variants are associated with symptomatic cerebrovascular disease in the general population. We demonstrated that they conferred a risk equivalent to that in the top 1.6% of individuals as determined by a polygenic risk score, with the risks from common polygenic variant and NOTCH3 variants being independent.…”
Section: Discussionsupporting
confidence: 61%
“…[4] Although CADASIL is considered rare, with a reported disease prevalence of 4 per 100,000, [5,6] recently a much higher frequency of typical cysteine-altering NOTCH3 variants, as high as 1 in 400. [7,8] These could contribute to the risk of apparently sporadic lacunar stroke, but the clinical significance of these variants remains uncertain. Studies have mostly been conducted on anonymised genome-sequencing databases, [7] and it is unclear whether such apparently 'asymptomatic' variants have clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, because of the creation of biobanks, which are projects that aggregate and harmonize exome and genome sequencing data from a wide variety of large-scale sequencing studies, it has been possible to further profile mutations affecting cysteine residues in Notch3 in a significant number of individuals. In the Genome Aggregation Database (gnomAD, , accessed on 27 May 2021), the UK Biobank (UKB, , accessed on 27 May 2021) and the Geisinger DiscovEHR ( , accessed on 27 May 2021), a prevalence of 1.4–3.4/1000 subjects carrying NOTCH3 variants that were considered pathogenic were established [ 17 , 18 , 19 , 20 , 21 ] ( Figure 2 ), and 9/1000 in the Taiwan Biobank ( , accessed on 27 May 2021) [ 22 ], the latter high frequency is in line with the UKB observation of enrichment of pathogenic mutations in NOTCH3 in Asians [ 19 ].…”
Section: Genome-wide Sequencing and Progress In Epidemiologymentioning
confidence: 99%